Asthma prevalence and control among schoolchildren residing near outdoor air pollution sites. (2nd January 2022) - Gentile, Deborah A.; Morphew, Tricia; Elliott, Jennifer; Presto, Albert A.; Skoner, David P.
Abstract: Introduction: Outdoor air pollution (OAP) contributes to poor asthma outcomes and remains a public health concern in Pittsburgh. The purpose of this study was to determine the prevalence of childhood asthma and its rate of control among Pittsburgh schoolchildren residing near OAP sites. Methods: Participants were recruited from schools near OAP sites. Asthma prevalence and control were assessed using a validated survey. Demographics and socioeconomic status were collected by survey, BMI was calculated, secondhand smoke (SHS) exposure was assessed by salivary cotinine levels, and OAP was assessed by mobile platform monitoring. Multivariate analysis adjusted for confounders. Results: In 1202 Pittsburgh elementary school students surveyed, 50.9% were female, average age was 8.5 years (SD = 1.9), 52.2% were African American and 60.6% had public health insurance. SHS exposure was relatively high at 33.9%, 17.1% of students were obese, and 70% had exposure to particulate matter (PM2.5 ) greater than the World Health Organization standard of 10 μg/m 3 . Overall prevalence of asthma was 22.5% with PM2.5, nitric oxide (NO x ), sulfur (S), and zinc (Zn) significantly related to odds of asthma. Among the 270 children previously diagnosed with asthma, 59.3% were not well controlled with PM2.5, black carbon, and silicon (Si) significantly related to odds of uncontrolled asthma. Conclusions: These results demonstrate that asthma prevalence and poor disease control are significantly elevated in Pittsburgh schoolchildren exposed to high levels of OAP. Future efforts need to focus on primary prevention of asthma by reducing exposure to OAP in at risk populations.